Pengaruh Curent Ratio dan Debt to Equity Ratio Terhadap Profitabilitas (Studi Pada PT Unilever Indonesia Tbk. Tahun 2012 - 2020) - Luh Putu Widyani Puspitawati, Ni; Utami Widya Astuty, Ratna; Saputra, Davit; Riadien, Pena; Frebiana Joe, Angelina; Suryani, Embun (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of the Current Ratio and Debt to Equity Ratio on profitability in Fast Moving Consumer Goods (FMCG) companies, specifically PT Unilever Indonesia Tbk., listed on the Indonesia Stock Exchange (IDX) for the 2012–2020 period. The sampling technique used is purposive sampling, and the data employed are secondary data. The analysis methods include classical assumption tests, autocorrelation tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, hypothesis testing, and determination coefficient testing using SPSS version 26.0 and Microsoft Excel 2019 with the stepwise method. The study results indicate that the Current Ratio and Debt to Equity Ratio have no significant effect on the company's profitability.